IMPLEMETASI KURIKULUM SEKOLAH MINGGU TERHADAP PERKEMBANGAN KEROHANIAN ANAK-ANAK SEKOLAH MINGGU DI GEREJA PANTEKOSTA DI INDONESIA MARANATHA YOSOMULYO BANYUWANGI - Yustani Harefa; Dr. Yehezkiel Sugeng Mulyono M.Th (Sekolah Tinggi Teologi Duta Panisal, 2023)
Basically, the Sunday School Curriculum has a very important role in the implementation of learning activities in Sunday School. The Sunday School curriculum is a Sunday School program that is systematically designed and used as a guideline in the child development process to achieve the goal of guiding children to grow in the knowledge of Jesus Christ as Lord and Savior. Pentecostal Church Sunday School in Indonesia Maranatha Yosomulyo Banyuwangi is one of the Sunday Schools that has used the Sunday School Curriculum. The Sunday School curriculum at the Pentecostal Church Sunday School in Indonesia, Maranatha Yosomulyo Banyuwangi, was implemented for the period July-September 2022. This study used a qualitative method with a case study approach. From the results of the research that was carried out after implementing the Sunday School Curriculum at the Pentecostal Church Sunday School in Indonesia, Maranatha Yosomulyo Banyuwangi, the researchers found that after the Sunday School Curriculum was in place, the preparation of teachers was much better because the materials to be taught to children had already been prepared. well structured in the Sunday School Curriculum and children are also more enthusiastic in participating in learning activities in Sunday School. With a well-organized learning system, it will help children to experience spiritual development properly